Circuit modelling of broadband antenna using vector fitting and foster form approaches for IoT applications - Ahmad, Sarosh; Parchin, Naser Ojaroudi; Al Gburi, Ahmed Jamal Abdullah; Ez-zaki, Fatima; Belaid, Khaoula Ait; Belahrach, Hassan; Ghammaz, Abdelilah (MDPI AG, 2022)
Computation of the broadband antenna impedance behavior requires the wideband lumped equivalent circuit. This work aims to provide a comprehensive study of broadband antenna equivalent circuit models over broad frequency ranges for Internet of Things (IoT) applications using multiple approaches. The first approach is a Foster approximation, which is based on the antenna-simulated scattering parameters and impedance data. The second concerns a vector-fitting fitting approximation, which is based on the antenna-simulated impedance/admittance data. The studied antenna is modeled based on the radiating element’s geometry and the multifractal slots, in addition to the DGS (Defected Ground Plane) effects. Applying these techniques, wideband lumped equivalent circuits of the antenna have been computed which are in good agreement with measurement data. These models could be useful for the enhancement of the performance of a broadband antenna and its systematic design as well as offering the advantage of saving computation time for full-wave simulations and facilitating the solution of problems that have both an electromagnetic part as well as a circuit part. For further analysis, the Gaussian pulse has been generated to drive a time-domain analysis of the current and power response waveforms antenna behavior under load.